2006
DOI: 10.1007/s10265-006-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of putative quantitative trait loci controlling the total oligosaccharide and sucrose content of Glycine max seeds

Abstract: Although oligosaccharides and sucrose are very important nutritional components of soybean seeds, little information is available about inheritance of oligosaccharide and sucrose content. The objective of this study was to identify quantitative trait loci (QTLs) that determine the oligosaccharide and sucrose content of soybean. The 117 F(2:10) recombinant inbred lines developed from a cross of "Keunolkong" and "Shinpaldalkong" were used. Narrow-sense heritability estimates, on a plot mean basis, of oligosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 14 publications
5
41
1
Order By: Relevance
“…In comparison with the reference 'Williams 82' physical map, these two QTL regions were within a similar proximity, with sucrose QTL in the F 3derived population being narrowed down to a smaller region in the SNP analysis (Table 8). In other studies, sucrose QTL were mapped by Kim et al (2005Kim et al ( , 2006 using data from only one location. In a previous study, a sucrose QTL flanked by Satt287 (at 1,631,658-1,631,885 bp of Gm16 in the Williams 82 physical map) and Sct_065 (at 10,498,889-10,499,048 bp of Gm 16, Williams 82) on chromosome 16 was identified by Kim et al (2006); this previously reported QTL was distantly located upstream from the QTL identified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the reference 'Williams 82' physical map, these two QTL regions were within a similar proximity, with sucrose QTL in the F 3derived population being narrowed down to a smaller region in the SNP analysis (Table 8). In other studies, sucrose QTL were mapped by Kim et al (2005Kim et al ( , 2006 using data from only one location. In a previous study, a sucrose QTL flanked by Satt287 (at 1,631,658-1,631,885 bp of Gm16 in the Williams 82 physical map) and Sct_065 (at 10,498,889-10,499,048 bp of Gm 16, Williams 82) on chromosome 16 was identified by Kim et al (2006); this previously reported QTL was distantly located upstream from the QTL identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The major sucrose QTL on chromosome 19 was flanked by SSR markers Satt278 and Satt523, which explained 21.4% of the total phenotypic variation for sucrose content, while the other two sucrose QTLs on chromosome 2 and 11 conferred minor effects. Using another RIL population derived from the cross of 'Keunolkong' ´ 'Shinpaldalkong', Kim et al (2006) found two QTLs located on chromosomes 12 and 16 significantly associated with sucrose content; however, these QTLs explained a relatively low amount of phenotypic variation (<10%) for sucrose content.…”
mentioning
confidence: 95%
“…The major QTL, flanked by SSR markers Satt278 and Satt523, located on chromosome 19 explained 21.4% of the total phenotypic variation in sucrose content, while the other two QTL on chromosome 2 and 11 conferred minor effects, respectively. Kim et al (2006) also reported two new QTL, located on chromosomes 12 and 16. These explained a relatively low amount of phenotypic variation (< 10%) in sucrose content.…”
mentioning
confidence: 91%
“…The QTL analysis in soybean located four QTL for oligosaccharide content. Total oligosaccharide and sucrose content in soybean has two common QTL in two linkage groups (LGs) (Kim et al 2006). The total amount of RFOs in Medicago truncatula was similar to that in pea and appears in a rank order system between the parents of the first mapping population LR1 (71.60 versus 75.16 μg/mg) and the parents of the second population LR4 (67.06 versus 59.98 μg/mg).…”
Section: Resultsmentioning
confidence: 88%
“…Maughan et al (2000) identified genomic regions significantly associated with quantitative trait loci (QTL) controlling sucrose content in soybean. In soybean four QTL for oligosaccharide content were identified (Kim et al 2006). In Medicago truncatula QTL mapping revealed one QTL that explained variation in the stachyose/verbascose ratio co-located with a stachyose synthase gene, determining the oligosaccharide composition (Vandecasteele et al 2011).…”
mentioning
confidence: 99%